Karakterisasi Pasir Besi (Fe3O4) Sungai Seruai Kabupaten Deli Serdang - Yusuf Lubis, Ridwan; Maharani Rangkuti, Dea; Lubis, Haryati; Masthura; Husnah, Miftahul (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2023)
In this research, iron sand was obtained from the Sei Serayu river in Deli Serdang Regency. The method for extracting iron sand is by manual extraction using a permanent magnet. The samples that have been obtained are then given temperature treatment with variations of 500 o C, 600 o C and 700 o C so that the iron sand undergoes oxidation. Next, the samples that have been heat treated are characterized using XRD, SEM and XRF. From the XRD test results it was found that the sample consisted of Fe3O4 with a magnetite phase. XRD diffraction peaks were obtained at angles 2θ: 17.26 o, 29.98 o, 35.4 o, 43.16 o, 57.08 o, and 62.56 o. SEM test results show that sample D contains magnetite (Fe3O4) with a silver color. Based on the analysis of test results, it can be concluded that the most optimal results are found in sample D with a sintering temperature of 700o C.